Communication Strategy Of Republic Of Indonesia Radio Broadcaster Medan In Attracting The Interest Of Listener - Mahendra, Ramadhan; Syahminan, Mhd; Ismail (International Journal of Cultural and Social Science, 2022)
This research begins with the existence of radio broadcasts which have begun to fade. But not with RRI Medan, which still exists by continuing to broadcast and having its own place in society. in Attracting Listeners' Interest. Informants in this study were KABID Broadcasting RRI Medan, Plh Administration, 6 broadcasters, and 2 listeners. The type of research used is qualitative research, using a descriptive approach. Data collection techniques use observation, interviews, and documentation. The communication strategy of the broadcaster of Radio Republik Indonesia Medan in attracting listeners is by doing several stages. First, the broadcasting process must run in accordance with the provisions that have been set. Second, the broadcaster's communication style based on educative, informative, and persuasive broadcasting techniques has its own differences and characteristics depending on what type of broadcast the broadcaster will bring. Third, the strategy of RRI Medan in formulating communicators (broadcasters), media, messages in attracting listeners. To attract listeners, broadcasters always insert motivating messages. Broadcasters also share radio broadcasts to social media such as Instagram, YouTube, and the RRIPlay Go application. The result, when viewed from the response of listeners to RRI Medan, the broadcaster's communication strategy of RRI Medan succeeded in attracting listeners. Listeners are attracted by the way broadcasters present broadcast programs. What makes listeners most comfortable is that the announcer can always get along with his listeners